Penerapan Permainan Gandang Tigo sebagai Materi Pelatihan Pada Ekstrakurikuler - Tomi, Krispra Tomi suharto; Ardipal (Universitas Negeri Padang, 2024)
This research aims to describe the application of the Gandang Tigo game as extracurricular training material at SMP N 24 Padang. This type of research is action research with a qualitative approach. Action research is an effort to improve understanding, methods and conditions carried out collaboratively. In qualitative research, data collection is carried out in natural conditions by means of observation, interviews and documentation. The conclusion from the results of this research is that the application of the Gandang Tigo game as training material in extracurricular activities can bring about changes in students, and also by planning the provision of varied extracurricular materials, it can provide space for expression according to students' interests and talents. Implementing extracurricular activities using varied materials can stimulate students to focus more on playing music and also increase individual abilities, and from the results of observations it can be seen that student responsiveness in musical form increases, because providing material with a difficult structure can increase students' focus in practicing. In the training process, evaluation activities aim to find out the extent of students' strengths and weaknesses, so that they can practice more actively.